Primary Hodgkin’s Lymphoma of the Sternum: Report of a Case and Review of the Literature - Jain, Ankur (J Clin Diagn Res, 2016)
Sternal masses present a unique diagnostic challenge in clinical practice. A wide array of differential diagnosis of a sternal mass includes osteomyelitis, tuberculosis, eosinophilic granuloma, sarcoma and lymphoma (usually Non-Hodgkin’s) amongst others. Sternum is a rare site of Hodgkin’s lymphoma and is usually misdiagnosed as tuberculosis or eosinophilic granuloma on routine histopathology. This delayed diagnosis culminates in death of patients. We report a 30-year-old lady who presented with swelling in upper part of chest wall since 1 month. Past history was significant for a similar swelling 2 years back, which was diagnosed as hodgkin’s lymphoma and treated with 4 cycles of chemotherapy at another centre (which led to resolution of the swelling). Examination revealed a 6x6.5cm firm swelling originating from the upper part of sternum. There was no lymphadenopathy or organomegaly. Histopathological examination (with immunohistochemistry) of the trucut biopsy from the swelling confirmed the diagnosis of Hodgkin’s lymphoma (nodular sclerosis). Patient was diagnosed as a late relapse of primary sternal Hodgkin’s lymphoma (stage IBE) and was administered 4 cycles of ABVD followed by local radiotherapy to the involved site which led to complete resolution of the disease as assessed by PET scan. We present this unusual case of primary sternal Hodgkin’s lymphoma. Rarity of this entity, with diagnostic challenges encountered and treatment options available are highlighted in the current report. A pubmed search revealed 18 cases of sternal involvement in Hodgkin’s lymphoma which have been tabulated.